The role of museum learning in promoting sustainability - Comparative research in Baranya County and Landkreis Görlitz - Koltai, Zsuzsa (Tudásmenedzsment, 2023)
The study explores aspects related to the role of museums in promoting sustainability among the results of a comprehensive research entitled „The role of museum learning in strengthening resilience in peripheral regions – Comparative research in Görlitz District and Baranya County” conducted with the support of the Saxon State Ministry of Science, Culture and Tourism's Saxon Visiting Professors Program 2022. Among the many aspects of the role of museums in promoting resilience, the empirical research also dealt with how much and in what way the museums/heritage sites in the two investigated areas contribute to the promotion of sustainability through their exhibitions, programs and other initiatives. Within the framework of the comparative research, based on a stratified sampling procedure, structured interviews were conducted with museum educators, museum directors, and relevant senior colleagues of 13 Baranya County and 13 Görlitz District museums/heritage sites between October 2022 and January 2023. The study compares the activities of the museums included in the research from the two regions in terms of the extent to which they promote the realization of the following seven of the 17 Sustainable Development Goals of the UN’s Agenda 2030: health and well-being, quality education, gender equality, reducing inequalities, responsible consumption and production, action against climate change, sustainable cities and communities.